(untitled) (Al Insyirah International Scientific Conference on Health, 2021)
Background: The number of sufferers of human immunodeficiency Virus (HIV)/ AIDS continues to increase every year. Prevention speared HIV/ AIDS on adolescence were needed. Purpose: The purposed this review was to identified intervention for prevention HIV/ AIDS on Adolescence population. Methods: This study used systematic review design. Search engine with Google Scholar, Pubmed, Proquest, and Ebscho host. Article published between 2019 until 2021. Inclusion criteria: English language, and program can applicated for adolescents (12-19 years old), adolescent without HIV/ AIDS. Exclusion criteria: adolescent with disorder or mental health, uncomplete project research, qualitative design, critical appraisal value under 50. Findings: There are no studies that focus on HIV / AIDS prevention intervention during the Covid-19 pandemic. However, there are 6 articles that discuss HIV / AIDS prevention in adolescents that can be adopted during the Covid-19 pandemic. Conclusion and Recommendation: The use of methods that pay attention to physical distancing such as telemedicine / tele-health can be adopted during a pandemic. However, what needs to be researched is the effectiveness of these interventions during the Covid-19 pandemic.